Repercussões do contato intergeracional no ambiente escolar - Hagen, Desirê Neuwald Pauletti (2016)
Studies focusing on intergenerational relations, with a consistent proposal of activities that foster the relationship between generations, promoting a gerontological awareness, are still scarce. A society in constant transformation in its age structure requires interventions able to raise a gerontological awareness based on respect, prejudice break, solidarity and on the construction of a new paradigm. Thus, this study aims to evaluate the implications of intergenerational contact experienced by schoolchildren and elderly people in the educational context. The study is a subproject of the study entitled "Gerontological education as a promoting strategy of multigenerational interaction for a healthy living and aging. The participants were preteen students of a school in the city of Passo Fundo and a group of elder women from the local community. As instruments, there were used: 1) a demographic characterization questionnaire; 2) the Todaro scale to assess children attitudes towards the elderly; 3) a rating scale of attitudes towards old age (Scheppard Inventory); and 4) workshops of intergenerational educational activities. The data were analyzed in two different ways, thus generating two scientific articles. Production I, entitled "Evaluation of the attitude of children and elderly who participated in intergenerational workshops", being a cross-sectional study of quantitative approach which enabled to envision that the attitudes of school children and the elderly benefited from intergenerational contact. Production II, entitled "Intergenerational experience in the school environment: results of a practice based on the performance of intergenerational educational activities", being a qualitative study, of the exploratory-descriptive type, which showed the benefit of intergenerational contact both for schoolchildren and the elderly.